Basis and limits of the prohibition of double jeopardy article 8 of the criminal code (2017)
The article 8 of colombian Penal Code establishes the prohibition of double jeopardy as a concretion in criminal matters of the fundamental right to non bis in idem esatblished in article 29 of the Political Constitution. According to the latter, all thos